Meningkatkan Hasil Belajar Siswa dalam PAK dengan Model PBL Fase D Kelas VIII di SMPN 2 Sebangki, Landak - Fran Tigor; Nerita Setiyaningtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research is titled "Improving Learning Outcomes in Catholic Religious Education Using the Problem-Based Learning (PBL) Model Phase D for Grade VIII at SMPN 2 Sebangki Landak." The purpose of this study is to enhance learning outcomes, increase the number of students achieving mastery, improve student focus on the material, and reduce tendencies toward hyperactivity through the implementation of the PBL model, particularly on the topic "The Church as a Sign and Means of Salvation." This study employs a qualitative approach in the form of Classroom Action Research (CAR), conducted in two cycles. The research subjects consist of 27 students. Data collection techniques include observation, interviews, documentation, and learning outcome tests. The results indicate that the implementation of the PBL model can improve students' average scores and the number of students achieving mastery. Additionally, students became more focused and active in learning, while hyperactive behavior decreased. The teacher plays a role as a facilitator in creating contextual and meaningful learning experiences. The PBL model has proven effective in fostering critical thinking skills and supporting the strengthening of the Pancasila Student Profile.